The Application of Awake-Prone Positioning Among Non-intubated Patients With COVID-19-Related ARDS: A Narrative Review - Chen, Lingli; Zhang, Yan; Li, Yi; Song, Chao; Lin, Fengyu; Pan, Pinhua (Frontiers in Medicine, 2022)
The coronavirus disease (COVID-19) pandemic has significantly increased the number of acute respiratory distress syndrome (ARDS) patients necessitating respiratory support. This strain on intensive care unit (ICU) resources forces clinicians to limit the use of mechanical ventilation by seeking novel therapeutic strategies. Awake-prone positioning appears to be a safe and tolerable intervention for non-intubated patients with hypoxemic respiratory failure. Meanwhile, several observational studies and meta-analyses have reported the early use of prone positioning in awake patients with COVID-19-related ARDS (C-ARDS) in improving oxygenation levels and preventing ICU transfers. Indeed, some international guidelines have recommended the early application of awake-prone positioning in patients with hypoxemic respiratory failure attributable to C-ARDS. However, its effectiveness in reducing intubation rate and mortality, applied timing, and optimal duration are unclear. High-quality evidence of awake-prone positioning for hypoxemic patients with COVID-19 is still lacking. Therefore, this article provides an update on the current state of published literature about the physiological rationale, effect, timing, duration, and populations that might benefit from awake proning. Moreover, the risks and adverse effects of awake-prone positioning were also investigated. This work will guide future studies and aid clinicians in deciding on better treatment plans.